Processing Sm-Fe(Ta)-N hard magnetic materials - Žužek Rožman, Kristina (Kovine zlitine tehnologije, 1999)
SmFe based alloys interstitially modified with nitrogen are potential candidates for high energy permanent magnets. >In order to obtain the optimum properties a thorough understanding of the starting material and processing parameters is required. The microstructures of two cast alloys of composition ?$Sm_{13,8}Fe_{82,2}Ta_{4,0}$? and ?$Sm_{13,7}Fe_{86,3}$? were carefully examined with a SEM equpped with EDX and the exact stoiciometries of the phases were determined. The SmFeTa material was found to contain significant amounts of ?$TaFe_2$?, as well as the ?$Sm_2Fe_{17}$?, ?$SmFe_2$?, ?$SmFe_3$? phases observed in the SmFe material but without the ?$α$?-iron dendrites which are characteristic of the latter material. Hydrogen absorption-desorption studies carried out on both materials have demonstrated the increased resistance to decomposition of the ?$Sm_2Fe_{17}$? material, requiring an additional 150°C for the reaction to go to completition. The optimum conditions necessary to provide the highest coercivities using the conventional HDDR process combined with pre-milling were investigated. The coercivities obtained afted using the HDDR process and subsequent nitriding without any pre-milling were 680 kA/m for the SmFeTaN and 360 kA/m for the SmFeN samples. Significantly higher coercivities of 1000 kA/m for SmFeN were achieved by reducing the particle size with millin prior to the HDDR process. The better coercivities obtained with the Ta containing sample were found to be due to the presence of a much smaller amount of ?$α$?Fe. The milling prior to the HDDR treatment improves the coercivity because of the small particle size, which prevents the grains going too large,with their consequent very negative effect on the coercivity.
Keywords: magnetne lastnosti; zlitine; samarij; železo; tantal; prahovi; koercitivnost